2015
DOI: 10.1002/jat.3153
|View full text |Cite
|
Sign up to set email alerts
|

In vitro neurotoxicity evaluation of piperazine designer drugs in differentiated human neuroblastoma SH‐SY5Y cells

Abstract: Abuse of synthetic drugs is widespread worldwide. Studies indicate that piperazine designer drugs act as substrates at dopaminergic and serotonergic receptors and/or transporters in the brain. This work aimed to investigate the cytotoxicity of N-benzylpiperazine, 1-(3-trifluoromethylphenyl)piperazine, 1-(4-methoxyphenyl)piperazine and 1-(3,4-methylenedioxybenzyl)piperazine in the differentiated human neuroblastoma SH-SY5Y cell line. Cytotoxicity was evaluated after 24 h incubations through the MTT reduction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 56 publications
(77 reference statements)
4
13
0
Order By: Relevance
“…Degradation of DNA following oxidative stress provoked by BZP and TFMPP was already reported (Arbo et al 2016;Persona et al 2016). On the other hand, reactive species are also able to target mitochondria, disturbing the sequestration of Ca 2+ within the mitochondrial matrix and impairing Δψm that is crucial for the functional integrity of mitochondrial electron transport chain and, therefore, for production of ATP by oxidative phosphorylation (Dias da Silva et al 2013a, c).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Degradation of DNA following oxidative stress provoked by BZP and TFMPP was already reported (Arbo et al 2016;Persona et al 2016). On the other hand, reactive species are also able to target mitochondria, disturbing the sequestration of Ca 2+ within the mitochondrial matrix and impairing Δψm that is crucial for the functional integrity of mitochondrial electron transport chain and, therefore, for production of ATP by oxidative phosphorylation (Dias da Silva et al 2013a, c).…”
Section: Discussionmentioning
confidence: 90%
“…Comparisons with results of other in vitro studies showed that immortalized hepatocytes display a lower threshold for susceptibility to BZP than CAKI-2 renal cells (EC 50 1.57 mg/mL, i.e., 8.91 mM) (Vaughan and Gautam 2011) but higher than H9c2 cardiomyocytes (EC 50 2.33 mM) (Arbo et al 2014) and SH-SY5Y neurons (EC 50 4.92 mM) (Arbo et al 2016). A similar trend was also found for TFMPP in those cell systems, but this drug displayed a significantly higher toxicity toward all cellular models (HepG2 EC 50 310 μM; HepaRG EC 50 450 μM; rat hepatocytes EC 50 140 μM; H9c2 cardiomyocytes EC 50 186 μM; SH-SY5Y neurons EC 50 386 μM) (Arbo et al 2014(Arbo et al , 2016Dias da Silva et al 2015). Accordingly, the results from the current study indicate that TFMPP is approximately 7× more detrimental than BZP to primary cells and 15× to HepaRG cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations